PEMANFAATAN SMARTPHONE SEBAGAI MEDIA BELAJAR MATA PELAJARAN BAHASA INGGRIS PADA MASA WABAH PANDEMI COVID-19 - Ely Mulyati; Ahmad Yani (JUPE : Jurnal Pendidikan Mandala, 2022)
Facing the Covid 19 outbreak that is currently sweeping our country and the world, it is highly hoped that teachers as the frontline in the world of education must be ready and able to adapt quickly and precisely.The use of smartphones as a learning tool during the current epidemic is very beneficial for teachers and students in carrying out the teaching and learning process so that the government's appeal for StayAtHome residents , in this case for students, does not actually take a day off from studying.Teachers can provide material to students via smartphones using available applications that can be downloaded and installed easily using the smartphones we have, including the Google Classroom application, the Zoom Cloud Meeting application and the Webex Meeting application.